Imaginary number challenge (3)

Algebra Level 4

( ( ( ( i 2 i ) 3 i ) 4 i ) ) 2016 i \large\left(\left(\left(\left(i^{2i}\right)^{3i}\right)^{4i}\right)^{\cdots}\right)^{2016i}

If the principal value of the expression above can be written in the form exp ( x ! π y ) \exp\left(\dfrac{x!\pi}y\right) where x x and y y are positive integers, find x + y x+y .

Details and Assumptions:

  • Every complex number z z can be written in the form z = r e i θ + 2 k π z=re^{i\theta+2k\pi} for some real r , θ r,\theta and all k k such that π < θ π -\pi\lt \theta\leq\pi . The value when k = 0 k=0 is called the principal value of z z .
  • i = 1 i=\sqrt{-1} denotes the imaginary unit.
  • exp ( x ) = e x \exp(x)=e^x where e e denotes the Euler's number .
  • n ! n! denotes the factorial function. For example, 8 ! = 1 × 2 × 3 × × 8 8! = 1\times2\times3\times\cdots\times8 .


The answer is 2018.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Tommy Li
Jun 23, 2016

e π 2 i = cos ( π 2 ) + i sin ( π 2 ) e^{\frac{\pi}{2}i}=\cos(\frac{\pi}{2})+i\sin(\frac{\pi}{2})

i = e π 2 i i=e^{\frac{\pi}{2}i}

i 2 i = ( e π 2 i ) 2 i = e 1 2 ( 2 ! ) ( π ) ( i 2 ) = e π i^{2i}=(e^{\frac{\pi}{2}i})^{2i}=e^{\frac{1}{2}(2!)(\pi)(i^{2})}=e^{-\pi}

( i 2 i ) 3 i = ( e π ) 3 i = e 1 2 ( 3 ! ) ( π ) ( i 3 ) = e 3 π i (i^{{2i})^{3i}}=(e^{-\pi})^{3i}=e^{\frac{1}{2}(3!)(\pi)(i^{3})}=e^{-3\pi i}

( ( i 2 i ) 3 i ) 4 i = ( e 3 π i ) 4 i = e 1 2 ( 4 ! ) ( π ) ( i 4 ) = e 12 π ((i^{{2i})^{3i}})^{4i}=(e^{-3\pi i})^{4i}=e^{\frac{1}{2}(4!)(\pi)(i^{4})}=e^{12\pi}

Observe the pattern :

( ( ( ( i 2 i ) 3 i ) 4 i ) ) n i = e 1 2 ( n ! ) ( π ) ( i n ) \large \left(\left(\left(\left(i^{2i}\right)^{3i}\right)^{4i}\right)^{\ldots}\right)^{ni}=e^{\frac{1}{2}(n!)(\pi)(i^n)}

( ( ( ( i 2 i ) 3 i ) 4 i ) ) 2016 i = e 1 2 ( 2016 ! ) ( π ) ( i 2016 ) \large \left(\left(\left(\left(i^{2i}\right)^{3i}\right)^{4i}\right)^{\ldots}\right)^{2016i}=e^{\frac{1}{2}(2016!)(\pi)(i^{2016})}

= e 2016 ! π 2 \large = e^{\frac{2016!\pi}{2}}

x + y = 2016 + 2 = 2018 \Rightarrow x+y=2016+2=2018

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...